The Combination of Ultraviolet-B and Vitamin K2 Exposure Effect on Fibroblast-like cell Number in Wistar Rats - Nelwan, Sindy Cornelia; Tedjosasongko, Udijanto; Dharmawan, Devi; Leo, Leviena Merlynike; Ardiana, Hana Ai; Rahmawati, Siti (Faculty of Dental Medicine Universitas Airlangga, 2023)
Background: Vitamin D deficiency in children is one of the problems most often discussed and received attention from around the world today, especially during the Corona virus disease-19 (Covid-19) pandemic. Vitamin D3 increases the production of vitamin K2 protein and activates a protein involved in bone metabolism. Vitamin K2 increases bone formation by stimulating osteoblast differentiation, regulating mineralization of the extracellular matrix, regulating bone marker gene expression, and inhibiting osteoclastogenesis. Purpose: to analyzed the effect of sun exposure, Ultraviolet-B (UV-B) and vitamin K2 supplementation on fibroblast-like cell as bone formation marker in Wistar rats (Rattus novergicus). Methods: twenty-four samples divided into 4 groups namely control group, UV-B group, vitamin K2 group, combination of UV-B and vitamin K2 group. After 21 days, extraction of lower incisors was done to examine fibroblast-like cell number